Integrated Metabolomics and Network Pharmacology Approach to Explain Possible Action Mechanisms of Xin-Sheng-Hua Granule for Treating Anemia - Pang, Han-Qing; Yue, Shi-Jun; Tang, Yu-Ping; Chen, Yan-Yan; Tan, Ya-Jie; Cao, Yu-Jie; Shi, Xu-Qin; Zhou, Gui-Sheng; Kang, An; Huang, Sheng-Liang; Shi, Ya-Jun; Sun, Jing; et al. (Frontiers in Pharmacology, 2018)
As a well-known traditional Chinese medicine (TCM) prescription, Xin-Sheng-Hua Granule (XSHG) has been applied in China for more than thirty years to treat postpartum diseases, especially anaemia. However, the underlying therapeutic mechanisms of XSHG for anaemia were still unclear. In this study, plasma metabolomics profiling for anaemia was firstly analyzed by UHPLC-QTOF/MS and multivariate data method. Using network pharmacology, the compound-target-pathway network of XSHG was constructed, so as to dissect anaemia-relevant signaling pathways. Finally, the crucial targets in the shared pathways of metabolomics and network pharmacology were experimentally validated by ELISA and Western Blot analysis. The results showed that XSHG could exert excellent effects on anaemia probably through regulating coenzyme A biosynthesis, sphingolipids metabolism, and HIF-1a signaling pathways, which was reflected by the increased levels of EPOR, F2, COASY, and the reduced protein expression of HIF-1a, SPHK1, and S1PR1. Our work successfully explained the polypharmcological mechanisms underlying the efficiency of XSHG on treating anaemia, and meanwhile, probed into the potential treatment strategies for anaemia from TCM prescription.